Commercially Prepared Antibiotic-Loaded Bone Cement and Infection Risk Following Cemented Primary Total Knee Arthroplasty. (18th November 2020) - Namba, Robert S.; Prentice, Heather A.; Paxton, Elizabeth W.; Hinman, Adrian D.; Kelly, Matthew P.
Abstract : Background: The efficacy of commercially available antibiotic-loaded bone cement (ABC) in preventing infection in total knee arthroplasty (TKA) is unclear. We sought to determine the effectiveness of commercially available ABC in reducing the risk of infection following TKA, both overall and among 3 subgroups of patients with a higher risk of infection (diabetes, body mass index ≥35 kg/m 2, and American Society of Anesthesiologists classification ≥3), and to evaluate the association between the use of ABC and the risks of aseptic revision and revision for aseptic loosening. Methods: The Kaiser Permanente Total Joint Replacement Registry was utilized to evaluate 87, 018 primary cemented TKAs performed from 2008 to 2016. The primary outcome was time to infection (90-day deep infection or septic revision). Reduced infection risk with ABC relative to regular cement was tested with use of propensity-score-weighted Cox proportional-hazards models with superiority and noninferiority testing. All analyses were replicated for each of the 3 high-risk subgroups. For the secondary revision outcomes, propensity-score-weighted Cox proportional-hazards models were utilized. Results: Regular cement was found to be noninferior to ABC with respect to risk infection (hazard ratio [HR], 1.14; 95% confidence interval [CI], 0.93 to 1.40) and cost across all TKA patients. However, a lower risk of infection was observed with ABC among TKA patients with diabetes (HR, 0.72; 95% CI, 0.52 to 0.99). There was no evidence of a difference in risk of revision for ABC compared with regular cement. Conclusions: We found that the additional cost associated with the use of commercially prepared ABC in primary TKA was not justified in all patients; however, the risk of reduction was lower among patients with diabetes who received ABC. Further study is warranted to identify the efficacy of ABC among other high-risk populations. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.